A study on application of SFCL in vietnam power distribution system with distributed generators (DGs) - Hung Chi Nguyen; Phuc Huu Nguyen (IAES Indonesian Section, 2019)
As the power load demand is rapidly increasing nowadays, many new power generation units are continuously connected to the power system such as small hydropower, wind power, solar cell, and so on. However, in a distribution system, the presence of Distributed Generators (DGs) would generally change the distribution system's behavior. This change can affect to the operation and protection of devices in power system and the original parameters will be deviated. Especially, the fault current of power system with DGs is dramatically increasing, and Superconducting Fault Current Limiter (SFCL) has attracted lots of attention as one of the best correctives to solve these issues. This paper proposes a strategy on application of SFCL in distribution system to solve the problems related to excessive short-circuit current and the mitigation of voltage sag due to the introduction of the DGs. Firstly, a Resistive-type SFCL (R_SFCL) is modeled by Matlab/Simulink. Next, a distribution system of Southern Vietnam power system is selected and simulated. Finally, according to the simulation results, the short circuit current and voltage sag improvements can be validated.